2022
DOI: 10.1088/1755-1315/989/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Baseflow separation using graphic method of recursive digital filter on Wae Batu Gajah Watershed, Ambon City, Maluku

Abstract: The most commonly used baseflow separation graphics method is the recursive digital filter. Choosing an RDF graphic filter method to estimate the base stream requires a sure accuracy. The application of the RDF graphics method on small island watersheds must take into account the unique hydrological conditions of small island watersheds with a small area of rain catch so that the RDF method approach can be applied. This research aims to analyze graphic methods for the hydrological characteristics of the small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Lyne and Holick, Chapman, Furey and Gupta, and Eckhardt algorithms are some of the most commonly used approaches. Latuamury et al [52] showed that Eckhardt's filters, a two-parameter digital filter performed better than the other algorithms for small island watersheds in Indonesia. Chapman et al [53] criticised the Lyne-Hollick filter method for assuming a constant baseflow during no quick flow.…”
Section: Flow Preparation-upper Rural Portionmentioning
confidence: 99%
“…Lyne and Holick, Chapman, Furey and Gupta, and Eckhardt algorithms are some of the most commonly used approaches. Latuamury et al [52] showed that Eckhardt's filters, a two-parameter digital filter performed better than the other algorithms for small island watersheds in Indonesia. Chapman et al [53] criticised the Lyne-Hollick filter method for assuming a constant baseflow during no quick flow.…”
Section: Flow Preparation-upper Rural Portionmentioning
confidence: 99%